EMPLOYEE PERFORMANCE MEASUREMENT MODEL WITH ROUGH SET APPROACH - Dori Mittra Candana (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Performance is a behavior that every person has as a work performance that is produced by employees in accordance with their role in the company. Timeliness, Effectiveness, Work Commitment and Independence are believed to be able to influence employee performance in achieving predetermined goals. Data mining has grown rapidly and adds value to information stored in databases. One of the fairly simple data mining algorithms is the Rough Set. The research application of the Rough Set algorithm is to analyze employee performance using the rought set method on the employees of Café Dapoer Enha Sago, Pesisir Selatan Regency by analyzing 10 employees with the results in this study are as follows; Based on the number of 10 samples of Dapoer Enha Sago employees who have been tested using the Rought set application, it can be seen that the results are that the performance appraisal of 10 Dapoer Enha Sago employees shows good results 3 employees and 7 employees who have very good performanc